Um estudo sobre jogos eletrônicos para o ensino de engenharia de software - Bastos, Gustavo David Leite (Universidade Federal de São Carlos, 2024)
The reviewed work converges on the point about software engineering, particularly in initial stages of computer education, being highly theoretical and abstract (CALDERÓN et al., 2017; CLEGG et al., 2017; MONTENEGRO et al., 2017; PETRI et al., 2017; PIEPER et al., 2017; ALATRISTA-SALAS & NUNEZ-DEL-PRADO, 2018; LARENAS et al., 2018; LÓPEZ-FERNÁNDEZ et al., 2022), which causes mass loss of interest and difficulty to learn its basic concepts and theories, amongst students, given the gap between in-class theory and real applications for that. However, software engineering is essential to reduce production and post-production costs and maintenance (people, time and money). To counter such a problem, different methods from different knowledge areas have been studied as complementary methods to motivate and facilitate the learning of SE. Two examples are gamification (applying game elements in a non-game context) and serious games (games with goals beyond entertainment - usually education or training of skills - in a safe environment). This work focuses on digital serious games and aims to survey which digital games are used to support SE learning/teaching and which areas of SE are supported by such games, as well as the means to evaluate and assess its impact on learning.
A study on electronic games for teaching software engineering
Keywords: Engenharia de software; Jogos eletrônicos; Ensino & aprendizagem; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO